(untitled) (The Review of Diabetic Studies, 2024)
Background Health care providers, medical laboratory and nursing professionals play vital roles in healthcare services. The increasing demand for quality and timely laboratory services and emerging technologies highlights the crucial need for continuing professional development and knowledge and attitude about used of laboratory. Despite this, there is limited information available regarding knowledge and attitude about used of laboratory in Saudi Arabia. Laboratory testing is an integral part of day-to-day primary care practice, with approximately 30 % of patient encounters resulting in a request. However, research suggests that a large proportion of requests does not benefit patient care and is avoidable. For a long time history and physical examination hare been the most important part of patient’s assessment However, in recent years, the care of patients has become increasingly dependent on the results of laboratory investigations, and clinical laboratories have become major component in the delivery of health care. Aim of the study: To assess the nurses knowledge and attitude towards utilization laboratory services at Saudi Arabia in 2024. Methods: cross-sectional study involving 100 medical laboratory professionals and nursing was conducted in Saudi Arabia from July to October 2024. An online structured self-administered questionnaire was used to collect information on the participants’ knowledge, attitudes. The questionnaire was designed to collect data on a number of variables related both to health services and providers and nursing staff. Results: the knowledge the majority of participant in high were (56.0%) about Utilization of laboratory among nursing followed by weak were (29.0%) while Range 15-23 and Mean +SD (16.255±4.012), while a significantly associated were P< 0.001 and X2 (104.24) , regarding the attitude the majority of participant positive attitude were (79.0%) while negative attitude were (21.0%) while Range 7-13 and Mean +SD (11.08±2.248), while a significantly associated were P< 0.001 and X2 (134.56) Conclusion the health care providers’ and nursing hold a favorable view of the knowledge and attitude about used of laboratory. Interventions such as educational strategies, feedback and changing test order forms may improve the efficient use of laboratory tests in Saudi Arabia, however, the level of evidence is quite low and the quality is poor.